2010 Fourth IEEE International Conference on Biometrics: Theory, Applications and Systems (BTAS) 2010
DOI: 10.1109/btas.2010.5634480
|View full text |Cite
|
Sign up to set email alerts
|

Human perceptual categorization of iris texture patterns

Abstract: We report on an experiment in which observers were asked to browse a set of 100 iris images and group them into categories based on similarity of overall texture appearance. Results indicate that there is a natural categorization of iris images into a small number of high-level categories, and then also into subcategories. Also, the categorization reflects the Caucasian / Asian ethnicity of the person. This iris texture categorization has potential application in, for example, creating an indexing algorithm to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…The study of employing iris on race categorization initiated from [124], which had used Gabor feature and Adaboost selection combination on a combined iris dataset for two-races classification. Their conclusion was that iris is race-related, a result which has been further confirmed by [125], [126], [127], [128], [129], [130], all of which fit well with race recognitions (Asian/Non-Asian, Asian/Black/Cucasian). Specifically, Qiu et al [125] studied the correlation between race and iris texture and concluded that race information is illustrated in iris texture features, with best classification rate of 88.3% by SVM.…”
Section: Iris Texturesupporting
confidence: 71%
“…The study of employing iris on race categorization initiated from [124], which had used Gabor feature and Adaboost selection combination on a combined iris dataset for two-races classification. Their conclusion was that iris is race-related, a result which has been further confirmed by [125], [126], [127], [128], [129], [130], all of which fit well with race recognitions (Asian/Non-Asian, Asian/Black/Cucasian). Specifically, Qiu et al [125] studied the correlation between race and iris texture and concluded that race information is illustrated in iris texture features, with best classification rate of 88.3% by SVM.…”
Section: Iris Texturesupporting
confidence: 71%
“…This human-machine pairing is important as human subjects can provide an incorrect decision even despite spending quite sometime observing many iris regions [120]. In addition, there has been a body of research showing that humans and machines do not perform similarly well under different conditions [20,108,154]. For example, Moreira et al also showed that machines can outperform humans in healthy easy iris image pairs; however, humans outperform machines in disease-affected iris image pairs [108].…”
Section: Human-machine Pairing To Improve Deep Learning-based Iris Re...mentioning
confidence: 99%
“…There are only a few works related to human examination of iris images. Stark et al [18] studied how people classify iris textures into categories. They used a software tool that allowed subjects to browse a set of segmented nearinfrared iris images and use a drag-and-drop scheme to organize the images into groups based on their perception of the iris textures.…”
Section: Related Workmentioning
confidence: 99%
“…The literature of iris recognition has been investigating the performance of humans at tasks such as iris texture perception [18,2,10,11,17] and identity verification [13,9]. Understanding how people perceive and analyze iris fea-tures is useful not only for inspiring the development of better solutions, but also for making them more humanintelligible.…”
Section: Introductionmentioning
confidence: 99%